Cortical responses to salient nociceptive and not nociceptive stimuli in vegetative and minimal conscious state - de Tommaso, Marina; Navarro, Jorge; Lanzillotti, Crocifissa; Ricci, Katia; Buonocunto, Francesca; Livrea, Paolo; Lancioni, Giulio E. (Frontiers in Human Neuroscience, 2015)
Aims Questions regarding perception of pain in non-communicating patients and the management of pain continue to raise controversy both at a clinical and ethical level. The aim of this study was to examine the cortical response to salient multimodal visual, acoustic, somatosensory electric non nociceptive and nociceptive laser stimuli and their correlation with the clinical evaluation. Methods: Five Vegetative State (VS), 4 Minimally Conscious State (MCS) patients and 11 age- and sex-matched controls were examined. Evoked responses were obtained by 64 scalp electrodes, while delivering auditory, visual, non-noxious electrical and noxious laser stimulation, which were randomly presented every 10 sec. Laser, somatosensory, auditory and visual evoked responses were identified as a negative-positive (N2-P2) vertex complex in the 500 msec post-stimulus time. We used Nociception Coma Scale-Revised (NCS-R) and Coma Recovery Scale (CRS-R) for clinical evaluation of pain perception and consciousness impairment. Results: The laser evoked potentials (LEPs) were recognizable in all cases. Only one MCS patient showed a reliable cortical response to all the employed stimulus modalities. One VS patient did not present cortical responses to any other stimulus modality. In the remaining participants, auditory, visual and electrical related potentials were inconstantly present. Significant N2 and P2 latency prolongation occurred in both VS and MCS patients. The presence of a reliable cortical response to auditory, visual and electric stimuli was able to correctly classify VS and MCS patients with 90% accuracy. Laser P2 and N2 amplitudes were not correlated with the CRS-R and NCS-R scores, while auditory and electric related potentials amplitude were associated with the motor response to pain and consciousness recovery. Discussion: pain arousal may be a primary function also in vegetative state patients while the relevance of other stimulus modalities may indicate the degre